The Philippines in the Economy of Southeast Asia - Mchale, Thomas R. (Silliman Journal, 2024)
Southeast Asia is fragmented not only by geography but also by history. Countries in the region are separated by jungles and seas and by their different colonial backgrounds. This is why there has been little economic cooperation between the Philippines and other countries in the area.